Serodiagnosis of human and animal pythiosis using an enzyme-linked immunosorbent assay. - Mendoza, L (1997)
Conventional serodiagnosis of Pythium insidiosum infections involves the use of the immunodiffusion (ID) test. This test specifically diagnoses human and animal pythiosis. The test, however, has limited sensitivity and does not detect some culturally proven cases of the disease. Because of the increased recognition of pythiosis among humans and animals, we developed and evaluated an enzyme-linked immunosorbent assay (ELISA) using a soluble antigen from broken hyphae of P. insidiosum. Studies were carried out with sera from five humans and eight animals with culturally and/or histologically proven pythiosis. Some of these sera were negative in the ID test for pythiosis. Heterologous case sera from thirteen humans and two horses, plus 5 sera from healthy humans and 17 from healthy animals, were tested. Of the pythiosis case sera tested, the ID test detected only 8 of 13 (61.5%), whereas the ELISA detected all of them (100%). The ID and ELISA tests were entirely specific and gave negative results or low titers respectively, with sera from humans and animals with heterologous fungal infections or with no apparent illness. No correlation was found between the height of the ELISA titers and negative or positive sera in the ID test. Our results indicate that the ELISA is a reliable serodiagnostic test for pythiosis. It is as specific as the ID test but more sensitive.